Spectroscopic and Mechanical Properties of a New Generation of Bulk Fill Composites - Monterubbianesi, Riccardo; Orsini, Giovanna; Tosi, Giorgio; Conti, Carla; Librando, Vito; Procaccini, Maurizio; Putignano, Angelo (Frontiers in Physiology, 2016)
The aims of this study were to in vitro evaluate the degree of conversion and the microhardness properties of five bulk fill resin composites; in addition, the performance of two curing lamps, for composites polymerization, was also analysed. Materials and Methods. The following five resin-based bulk fill composites were tested: SureFil SDR®, Fill Up!TM, FiltekTM , SonicFill TM and SonicFill2TM. Samples of 4 mm in thickness were prepared using Teflon molds filled in one increment and light-polymerized using two LED power units. Ten samples for each composite were cured using Elipar S10 and ten using Demi Ultra. Additional samples of SonicFill2 (3 and 5 mm-thick) were also tested. The degree of conversion (DC) was determined by Raman spectroscopy, while the Vickers microhardness (VMH) was evaluated using a microhardness tester. The experimental evaluation was carried out on top and bottom sides, immediately after curing (t0), and, on bottom, after 24 hours (t24). Two-ways analysis of variance was applied to evaluate DC and VMH values. In all analyses, the level of significance was set at p< 0.05. Results. All bulk fill resin composites recorded satisfactory DCs on top and bottom sides. At t0, the top of SDR and SonicFill2 showed the highest DCs values (85.56±9.52 and 85.47±1.90, respectively), when cured using Elipar S10; using Demi Ultra, SonicFill2 showed the highest DCs values (90.53±2.18). At t0, the highest DCs values of bottom sides were recorded by SDR (84.64±11.68), when cured using Elipar S10, and Filtek (81.52±4.14), using Demi Ultra. On top sides, Demi Ultra lamp showed significant higher DCs compared to the Elipar S10 (p<0.05). SonicFill2 reached suitable DCs on bottom 5mm-thick samples. At t0, VMH ranged between 24.4 and 69.18 for Elipar S10, and between 26.5 and 67.3 for Demi Ultra. Using both lamps, the lowest VMH values were shown by SDR, while the highest values by SonicFill2. At t24, all DC and VMH values significantly increased. Conclusions. Differences in DC and VMH among materials are suggested to be material and curing lamp dependent. Even at t0, the high viscosity bulk composites showed higher VMH than the flowable or dual curing composites.